THE INFLUENCES OF FINANCIAL, ENTREPRENEURIAL EDUCATION, AND SOCIAL SUPPORT TOWARDS WOMEN ENTREPRENEUR’S PERFORMANCE - Genoveva Genoveva; Bernadette Gaby (JIMFE (Jurnal Ilmiah Manajemen Fakultas Ekonomi), 2020)
The aim of this research is to find out the influence of source of finance, entrepreneurial education, and social support towards business performance of women SMEs in Jakarta area. A total of 146 valid online questionnaires were obtained to test used SPSS ver.25. Financial, Entrepreneurship Education, and Social Support are the independent variables while Women Entrepreneurs’ Performance is the dependent variable. The questionnaire used Likert scale (1) Strongly Disagree – (5) Strongly Agree) with the snowball sampling method in Jakarta area only. Data analysis is done through validity and reliability test, followed by classic assumption test as well as multiple regression, both to confirm the hypotheses. The result confirms that source of finance, entrepreneurial education, and social support influence significantly on the performance of women SMEs.